Multicultural Education in Indonesia: An Analytical Study of Azyumardi Azra’s Thought in Strengthening National Pillars - Mohamad Kholil; Rifqi Rifqi (Lentera Peradaban: Journal on Islamic Studies, 2025)
The phenomenon of Indonesia's national diversity and its accompanying challenges serve as the compelling background for this research. The existence of various religions and belief systems is one of many aspects of this diversity, which at certain points, often triggers conflict and violence. Inter-ethnic and inter-religious conflicts in several regions of Indonesia reflect a lack of understanding among parts of society in responding to such plurality. Therefore, an in-depth study of educational implementation in Indonesia, specifically multicultural-dimensioned religious education, is crucial for addressing horizontal conflicts driven by religious or ethnic sentiments. In this context, Azyumardi Azra is a prominent Muslim scholar whose thoughts are deeply concerned with these issues. This research is a library study using a qualitative biographical approach. The method employed is content analysis to understand and identify the substance of Azyumardi Azra's multicultural education thoughts found across various literary sources. The results indicate: (1) In Azra's view, multiculturalism leads to a conscious affirmation that all forms of diversity and difference hold equal standing in the public sphere. Multiculturalism goes beyond a mere understanding of plurality. The core values developed in Azra’s perspective include plurality, equality, humanity, justice, and democratic values; (2) According to Azra, multicultural education is education for or about social diversity aimed at fostering unity amidst diversity. Azra’s concept of multicultural education is rooted in the reality of Indonesia's national diversity to strengthen the four pillars of the nation: Pancasila, the Unitary State of the Republic of Indonesia (NKRI), the 1945 Constitution, and Bhinneka Tunggal Ika.